Osteosynthesis of a Multifragment Femoral Shaft Fracture and Peri-Implant Refracture in an 83-Year-Old Patient with Osteogenesis Imperfecta - Tobias M. Ballhause; Roland Gessler; Matthias H. Priemel; Karl-Heinz Frosch; Carsten W. Schlickewei (Case Reports in Orthopedics)
Introduction. Osteogenesis imperfecta (OI) is the term for a heterogenic group of conatal diseases that affect the bone formation. Eight different OI types are known. Patients with types III and IV frequently suffer from fractures without adequate trauma. The literature gives plenty advice for fracture treatment in pediatric OI patients, but there is less for adults, and no recommendations can be found for geriatric OI patients. Case Presentation. We report on an 83-year-old male who suffered from OI type IV. He was able to walk with an individually adapted gait orthosis. In an accident, the patient sustained a distal, multifragment, femoral shaft fracture. The fracture was openly reduced and fixated with a retrograde inserted elastic stable intramedullary nail (ESIN). Three months later, the patient was capable of walking without crutches. Due to another accident, he sustained a peri-implant refracture without failure of the ESIN. We immobilized the leg, and it achieved bony healing without reosteosynthesis. Eleven weeks later, he was again able to mobilize himself with full weight bearing. Discussion. We present a unique case of osteosynthesis in a distal, multifragment, femoral shaft fracture in a geriatric OI patient. No recommendations for the treatment of mature patients with OI can be found in the literature. We present our treatment concept and technique of osteosynthesis with an ESIN. Despite another accident with a peri-implant refracture, sufficient bony healing occurred, which allowed the patient to freely mobilize himself again.